Assessment and projection of the groundwater drought vulnerability under different climate scenarios and land use changes in the Sanjiang Plain, China - Zihan Ling; Longcang Shu; Dingkui Wang; Chengpeng Lu; Bo Liu (Journal of Hydrology: Regional Studies, 2023)
Study Region: A district of the Sanjiang Plain, China. Study focus: Aiming at assessing the likelihood of groundwater exposure to drought in the present and future, a comprehensive evaluation framework based on the groundwater drought vulnerability index (GDVI) is proposed. Firstly, nine influencing factors are selected in terms of groundwater dependence, hydrogeology, and meteorology, and the current drought vulnerability is assessed by combining the analytic hierarchy process (AHP) and random forest (RF) models. Afterwards, by projecting land use and future climate under the shared socioeconomic pathways of SSP1–2.6, SSP2–4.5, and SSP5–8.5, the GDVI is calculated for three future periods, i.e., 2015–2039, 2040–2064, and 2065–2089. New hydrological insights for the region: More than 30% of the groundwater experiences high and very high vulnerability during the baseline period, concentrated in areas with arable land and a thick clay cover. With rising temperatures and the rapid expansion of paddy fields, areas of high-vulnerability will continue to expand and will exceed 50% by the middle of the 21st century. If the groundwater irrigation and the agricultural land development are not restricted, the groundwater drought will be exacerbated. The proposed evaluation framework can be used in other areas with high groundwater use or where groundwater resources are at risk of depletion, and the findings provide guidance for agricultural development planning and joint surface water-groundwater scheduling.